2001
DOI: 10.1103/physrevlett.87.085504
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Reentrant Twist Grain Boundary Phase

Abstract: We report the occurrence of a reentrant twist grain boundary phase, which we designate as Re- TGB(A). Microscopic observations on a nonsymmetric dimer showed the phase sequence Iso- N*- TGB(A)-Sm- A-Re- TGB(A)- TGB(C*). Here N* and Sm- A stand for the chiral nematic and smectic- A phases, TGB(A) is the twist grain boundary phase with smectic- A blocks, and TGB(C*) that with smectic- C* blocks and exhibiting features of both the smectic- C* and TGB phases. The reentrance of the TGB(A) phase is unambiguously dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Later it was observed in pure systems as well [21,59]. In 1997, Pramod et al discovered a phase having two-dimensional undulation of the SmC Ã -like blocks in the form of a square lattice in binary mixtures of the chiral compound 4-(2 0 -methyl butyl phenyl 4 0 -n-octyl biphenyl-4-carboxylate (CE8) and 2-cyano-4-heptyl-phenyl-4 0 -pentyl-4-biphenyl carboxylate (7CN5) [60].…”
Section: Other Types Of Tgb Phasesmentioning
confidence: 91%
See 3 more Smart Citations
“…Later it was observed in pure systems as well [21,59]. In 1997, Pramod et al discovered a phase having two-dimensional undulation of the SmC Ã -like blocks in the form of a square lattice in binary mixtures of the chiral compound 4-(2 0 -methyl butyl phenyl 4 0 -n-octyl biphenyl-4-carboxylate (CE8) and 2-cyano-4-heptyl-phenyl-4 0 -pentyl-4-biphenyl carboxylate (7CN5) [60].…”
Section: Other Types Of Tgb Phasesmentioning
confidence: 91%
“…Shankar Rao et al (2001) have reported a re-entrant TGBA phase in a cholesterol based non-symmetrical dimer, namely cholesteryl 6-[4-(4-hexyloxyphenylethynyl) phenoxy] hexanoate [21]. Pressure-induced TGBA phase between N Ã and SmA phases has also been reported [22].…”
Section: Experimental Observation Of Tgba Phasementioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore we prepared a nonsymmetric dimer by joining a cholesteryl ester moiety to a 4-n-hexyloxytolane group (diphenylacetylene having an n-hexyloxy tail) through an n-pentyl (C 5 ) spacer. Interestingly this dimer showed a reentrant twist grain boundary phase (with smectic A blocks; TGB A ) and a newly discovered twist grain boundary phase (with smectic C* blocks; TGB C* ) [6]. More recently Jin et al…”
Section: Introductionmentioning
confidence: 97%